ULIL AMRI AUTHORITY ON LIMITATION OF CONGREGATIONAL WORSHIPS IN THE PANDEMIC OF COVID-19 IN PERSPECTIVE OF FIQH SIYASAH - Mustafa MH. (Jurnal Al-Dustur, 2020)
ABSTRACTThis article discusses the issue of limiting worship of Muslims in Indonesia, during the COVID-19 pandemic, which is regulated by Ulil Amri in Indonesia, namely the Government and Majelis Ulama Indonesia. In the regulation of restrictions on worship, it is not implemented as it should. There is a group of Muslim communities, which do not comply with the policy. This article is a literature study with a qualitative approach. The data in this study were produced from literature processing from various views of fuqaha, which is viewed from the perspective of fiqh siyasah. The results of the study concluded that Ulil Amri has full authority on social and ijtihadi (furu) issues, but not on the subject matter (ushul) of religion because it is the authority of Allah SWT as al-Shari '(maker of the Shari'a). Included in the Ulil Amri authority is issuing policies in preventing and overcoming the spread of the coronavirus in Indonesia, by implementing a policy of limiting worship, based on the fatwa from Majelis Ulama Indonesia, and with regulations issued officially by the Government.Keywords: COVID-19; Ulil Amri Authority; Worship Restrictions, Islamic Law